Implementation of Order-Taker SOP and Implications on Room Attendant Work Efficiency at the Alana Hotel and Convention Center Solo - Aulia, Nur; Darmaesti; Sugiman (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
,This study investigates the implementation of the Standard Operating Procedure (SOP) for order takers and its implications for the efficiency of room attendants in hotel housekeeping operations, with a case study at The Alana Hotel and Convention Center Solo. Within housekeeping services, order takers play a pivotal role as intermediaries between guests and room attendants, ensuring that requests and complaints are effectively communicated. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that the SOP for order takers has generally been implemented in accordance with established procedures, yet challenges remain in coordination and the timeliness of information delivery. The implementation of the SOP demonstrates a significant impact on room attendant efficiency, as reflected in improved service punctuality and a reduction in errors when responding to guest needs. The study concludes that optimizing order taker functions through clear SOP guidelines and regular training programs can enhance overall housekeeping performance. Beyond its managerial implications, this research contributes to the hospitality industry by promoting more efficient and professional service delivery. In addition, the results provide educational insights for prospective hotel employees and emphasize the importance of work ethics, teamwork, and operational effectiveness in service industries.